Coronavirus Usurps the Autophagy-Lysosome Pathway and Induces Membranes Rearrangement for Infection and Pathogenesis - Liang, Haowei; Luo, Dan; Liao, Hai; Li, Shun (Frontiers in Microbiology, 2022)
Autophagy is a crucial and conserved homeostatic mechanism for early defense against viral infections. Recent studies indicate that coronaviruses (CoVs) have evolved various strategies to evade the autophagy-lysosomes pathway. In this mini-review, we describe the source of double-membrane vesicles during CoVs infection, which creates a microenvironment that promotes viral RNA replication, virion synthesis and protects the viral genome from detection by the host. Firstly, CoVs hijack autophagy initiation through non-structural proteins and open reading frames, leading to the use of non-nucleated phagophores and omegasomes for autophagy-derived double-membrane vesicles. Contrastingly, membrane rearrangement by hijacking ER-associated degradation machinery to form ER-derived double-membrane vesicles independent from the typical autophagy process is another important routine for the production of double-membrane vesicles. Furthermore, we summarize the molecular mechanisms by which CoV non-structural proteins and open reading frames are used to intercept autophagic flux and thereby evade host clearance and innate immunity. A comprehensive understanding of the above mechanisms may contribute to developing novel therapies and clinical drugs against coronavirus disease 2019 (COVID-19) in the future.